2021
DOI: 10.3390/ani11092715
|View full text |Cite
|
Sign up to set email alerts
|

Partial and Total Replacement of Soybean Meal with Full-Fat Black Soldier Fly (Hermetia illucens L.) Larvae Meal in Broiler Chicken Diets: Impact on Growth Performance, Carcass Quality and Meat Quality

Abstract: The aim of this study was to compare selected growth performance parameters and slaughter characteristics in broiler chickens fed diets with a different content of full-fat Hermetia illucens L. (HI) larvae meal. The experiment was performed on 384 male broiler chickens (Ross 308) reared to 42 d of age and assigned to four dietary treatments (HI0—control diet and diets where soybean meal protein (SBM) was replaced with HI protein in 50%, 75% and 100%, respectively). The final body weights of chickens were as fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 51 publications
2
31
1
Order By: Relevance
“…Control group chickens were fed diets without PAP- HI (0 PAP- HI ), whereas birds in three experimental groups received diets where SBM protein was replaced with PAP- HI in the amount of 50% (50% PAP- HI ), 75% (75% PAP- HI ) and 100% (100% PAP- HI ). The ingredients, chemical composition and energy value of diets fed to broiler chickens are presented in our previous paper [ 15 ]. The fatty acid profile of HI larvae meal is shown in Table 1 , whereas the fatty acid profile of diets is presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Control group chickens were fed diets without PAP- HI (0 PAP- HI ), whereas birds in three experimental groups received diets where SBM protein was replaced with PAP- HI in the amount of 50% (50% PAP- HI ), 75% (75% PAP- HI ) and 100% (100% PAP- HI ). The ingredients, chemical composition and energy value of diets fed to broiler chickens are presented in our previous paper [ 15 ]. The fatty acid profile of HI larvae meal is shown in Table 1 , whereas the fatty acid profile of diets is presented in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Broiler chickens (2 birds/pen, 16 birds/treatment, 64 birds in total) were slaughtered at 42 days of age (stunning with the electrical water-bath stunner with 0.12 mA per bird applied for minimum 4 s and bleeding by severing the jugular vein). Their growth performance and selection for slaughter are presented in our previous paper [ 15 ]. After post-slaughter processing, the carcasses were chilled at 4 °C for around 24 h. Chilled carcasses were dissected, and the Pectoralis major ( PM ) muscles were cut out.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, results on organ weights and organ histology when BSFLM is included in higher amounts (>50% inclusion) are also variable. Some researchers did not observe any changes in organ weights or organ tissue histology ( Onsongo et al, 2018 ; Velten et al, 2018 ; Schiavone et al, 2019 ), whereas Murawska et al (2021) observed an increase in liver weight when replacing 75% SBM with BSFLM. Changes to organ weight are indicative of further health concerns, and therefore can aid in deducing information on the impact of BSFLM on broiler chickens.…”
Section: Introductionmentioning
confidence: 95%
“…Previous researchers that included BSFLM below ∼30% replacement of SBM observed no change or improved growth performance of broilers, including BW, feed intake ( FI ), and feed conversion ratio ( FCR ) ( Cullere et al, 2016 ; Dabbou et al, 2018 ; Onsongo et al, 2018 ; Schiavone et al, 2019 ; de Souza Vilela et al, 2021 ). However, some studies implementing BSFLM levels greater than ∼30% replacement of SBM, more notably with levels above ∼50%, resulted in reduced growth performance through lower BW, FI, and FCR as compared to lower inclusion rates ( Dabbou et al, 2018 ; Onsongo et al, 2018 ; Velten et al, 2018 ; Schiavone et al, 2019 ; Murawska et al, 2021 ). Additionally, results on organ weights and organ histology when BSFLM is included in higher amounts (>50% inclusion) are also variable.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging studies have shown that, in some fodders, it can replace fish or soy protein in proportions varying between 25–100%, depending on the species and age category [ 18 , 25 ], and fish oil up to 100% [ 26 ]. Although the bioproductive implications of some biologically active compounds and their impact on the quality of animal products and by-products require further studies [ 27 , 28 , 29 , 30 ], all these authors recommend the use of H. illucens protein meal and oil in the diet of farmed species [ 31 , 32 , 33 , 34 , 35 , 36 ]. Some qualitative shortcomings of H. illucens protein meal and oil can be overcome by manipulating the structure of the larval growth substrate, which can significantly change the nutrient composition of the larvae [ 37 , 38 , 39 , 40 ].…”
Section: Introductionmentioning
confidence: 99%